Management of the Mental Hospital - Dr , Hitesh C Sheth (International Journal of Psychosocial Rehabilitation, 2013)
There are multiple challenges; one comes across when one manages the facilities that house mentally ill patients. The chal- lenges include maintenance of physical infrastructure, including water and drainage systems; to protect the human rights of mentally ill patients admitted in such facilities and the management of the staff working in the institution. These challenges are going to exacerbate in future because mentally ill patients are increasing day by day, while the facilities that can house them and treat them, are not increasing in the same proportion. We need novel approaches and active government interven- tions, both physically as well as financially, to avert this impending humanitarian crisis.